Content and value of rehabilitation in dermatology. (3rd February 2021) - Voigt, Tilmann Peter; Bause, Leonie; Tsianakas, Athanasios
Summary: The therapy of chronic skin diseases is challenging for both the dermatologist and the patient. Current standards of therapy and individual circumstances of the patient have to be considered. Furthermore, chronic skin diseases are often associated with comorbidities that require treatment adapted to the individual. Therefore, optimal education of the patient and a holistic concept of therapy are needed, in many cases in collaboration with various medical disciplines. In this case, rehabilitation provides an opportunity to address important aspects such as comorbidities, psychosocial burden and limitations at work, in addition to treating the underlying disease. This article describes the differences between acute and rehabilitation health care in dermatology, and illustrates the importance of rehabilitation in dermatology, based on examples of chronic inflammatory skin diseases, chronic pruritus and dermato‐oncological diseases.